Use of Interactive Multimedia to Improve Digital Literacy in Elementary Schools - Ramadhani, Rahmi Putri; Setyowati, Rr Nanik; Kristanto, Andi (International Journal of Emerging Research and Review, 2024)
Objective: Technological developments in the industrial era 4.0 have had a significant impact on the transformation of education. The use of interactive multimedia in elementary schools is one of the important steps to prepare students to face the demands of the digitalization era. Method:  This research uses descriptive qualitative methods with stages including data collection, data reduction, data display, and conclusion drawing or verification. The data collection technique carried out is secondary data, namely data collected indirectly on the object being studied in the form of several national and international journals that can be accounted for. The purpose of this study is to explain how the use of interactive multimedia can improve learners' ability in digital literacy skills. Keywords such as interactive multimedia, concept understanding, and digital literacy were used to select this research article.  Results: The result of this study is that the use of interactive multimedia in learning can improve digital literacy skills in elementary school students. The use of interactive multimedia in improving digital literacy in elementary schools brings many novelties that can provide a more dynamic and effective learning experience. Novelty: By continuing to integrate this interactive learning multimedia innovation in basic education, it is expected that students can be better prepared to face the demands of digital literacy in today's digital era.